Layanan Bimbingan Dan Konseling Pada Siswa Sekolah Dasar Di Samarinda - Andi Alif Tunru; Rahmat Ilahi; Refi Winda Anjani Putri (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2022)
This study aims to determine the function of Guidance and Counseling Services for Elementary School Students in Samarinda. The approach used in this study is a qualitative approach by collecting data through observation, interviews, documentation, using teachers and students as informants. Then the data analysis was carried out with several stages such as data reduction, data presentation, and drawing conclusions based on the data that had been collected. Based on the research that has been carried out, it was found that the Guidance and Counseling function was carried out by class teachers according to the points of the guidance and counseling function, but there was one point that was not implemented, namely the distribution function due to Covid-19.